2011
DOI: 10.1103/physreve.83.041113
|View full text |Cite
|
Sign up to set email alerts
|

Force measurement in the presence of Brownian noise: Equilibrium-distribution method versus drift method

Abstract: The study of microsystems and the development of nanotechnologies require alternative techniques to measure piconewton and femtonewton forces at microscopic and nanoscopic scales. Among the challenges is the need to deal with the ineluctable thermal noise, which, in the typical experimental situation of a spatial diffusion gradient, causes a spurious drift. This leads to a correction term when forces are estimated from drift measurements [G. Volpe, L. Helden, T. Brettschneider, J. Wehr, and C. Bechinger, Phys.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 33 publications
(60 reference statements)
5
73
1
Order By: Relevance
“…In our case, Dt should meet the condition Dt ) t; d, which warrants that the data are subsampled with respect to the fast time scales of the process we consider and therefore the estimation of the drift and diffusion of the homogenized low-dimensional model is correct 30 . Furthermore, Dt should also be much smaller than the relaxation time of the system 25 . Both conditions are verified in the experiments presented in this article by subsampling the experimental data at Dt ¼ 10 ms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, Dt should meet the condition Dt ) t; d, which warrants that the data are subsampled with respect to the fast time scales of the process we consider and therefore the estimation of the drift and diffusion of the homogenized low-dimensional model is correct 30 . Furthermore, Dt should also be much smaller than the relaxation time of the system 25 . Both conditions are verified in the experiments presented in this article by subsampling the experimental data at Dt ¼ 10 ms.…”
Section: Methodsmentioning
confidence: 99%
“…This shift of the equilibrium is a consequence of the non-uniformity of S(y) ( presence of a multiplicative feedback. We remark that S(y) is independent from the interpretation of the underlying SDE 25 . D(y) (symbols in Fig.…”
mentioning
confidence: 99%
“…43 Indeed, recent experiments showed that neglecting the drift velocity leads to an erroneous qualitative evaluation of the conservative forces acting on Brownian spheres. 44 We would like to point out that the presence of a "drift" velocity does not mean that there is a net particle flux in the velocity direction. The drift velocity is, instead, an effect of the variation of the particle mobility with the configuration of the system, and its adequate evaluation is required to obtain the correct particle equilibrium distribution.…”
Section: Spheroid Drift Velocitiesmentioning
confidence: 99%
“…How to deal with these cases is explained in Refs. [13,14]. Similar considerations hold also in the case of diffusion gradients induced by, e.g., chemical gradients or temperature gradients [15,16,17].…”
Section: Diffusion Gradientsmentioning
confidence: 61%